EFEITOS DA VENTILACAO COM PRESSAO POSITIVA INTERMITENTE E CONTINUA SOBRE A FUNCAO RENAL EM CAES, COM DIFERENTES NIVEIS DE PRESSAO PARCIAL DE CO2 ARTERIAL - Vianna, P. T.G.; Cerqueira Braz, J. R.; Lopes De Carvalho, I.; Castiglia, Y. M.M. (My University, 1979)
The authors studied the effects of intermittent positive pressure ventilation (IPPV) and of continuous positive pressure ventilation (CPPV) on the renal function of 18 mongrel dogs. The animals were separated into three groups: Group II - Normocapnia - PaCO2 = 38 mmHg; Group I - Hypocapnia - PaCo2 = 25 mmHg; Group III - Hypercapnia - PaCo2 = 65 mmHg. In all the animals the extracellular volume was expanded with saline solution. The measurements were made during IPPV (moment zero), CPPV of 5 cm H2O (moment 5) and CPPV of 10 cm H2O (moment 10). Based on the results, the authors concluded that renal function tests were normal in Group II. The same didn't happen in groups I and III, which showed renal function modifications, attributed to the hemodynamic changes produced by VPPC.
Effects of intermittent and continuous positive pressure ventilation on renal function in dogs with various levels of arterial PCO2